DOP30 Long-term outcomes of Crohn's perianal fistulas treatment: anti-TNF with surgical closure versus anti-TNF alone (PISA-II) - A patient preference RCT. (21st January 2022) - Meima - van Praag MD, E; Stoker, J; D'Haens, G; Gecse, K; Dijkgraaf, M; Bemelman, W; Buskens, C
Abstract: Background: The PISA-II trial showed that anti-TNF induction combined with surgical closure induces MRI healing more frequently than anti-TNF alone at 18 months follow-up (FU) and that this was associated with no recurrences at the time. The aim of this study was to compare long-term outcomes of both treatment arms. Methods: In this FU study, data were collected from patients who participated in the PISA-II trial, a multicentre, international patient preference randomised controlled trial that compared anti-TNF induction combined with surgical closure to anti-TNF therapy alone as treatment for Crohn's perianal fistulas. FU data were collected from the time of enrolment in the PISA-II trial until November 2021. Primary outcome was radiological healing at MRI and secondary outcomes included long-term clinical closure, recurrences, anti-TNF trough levels (suboptimal level was defined as infliximab <5.0ug/ml, adalimumab <5.9ug/ml), incontinence (improved, decreased or never had), and a decisional regret scale. Results: Long-term FU data were collected from 88 out of 94 patients included in the PISA-II trial, 35/38 in the surgical closure arm and 53/56 in the anti-TNF treatment arm. Median FU was 5 years (IQR 4–7). During long-term FU radiological healing occurred in significantly more patients in the surgical closure arm (40% vs 17%; P=0.018). Long-term clinical closure occurred in 71% in the surgical closure arm and in 60% in the anti-TNF treatment arm (P=0.533). Recurrences occurred in 20% in the surgical closure arm and in 36% in the anti-TNF treatment arm (P=0.111). One patient with radiological healing developed a recurrence (4.3%) vs 12/57 (21.1%) patients with clinical closure. Trough levels were available in 32/53 patients treated with anti-TNF. Around the time of recurrence a suboptimal anti-TNF serum trough level occurred in 6/10. In the surgical closure arm, 6 patients had more and 6 patients had less incontinence problems after treatment, comparable to the 5 patient in the anti-TNF treatment arm with more and 8 with less incontinence problems. All patients in the surgical closure arm who completed the questionnaire (strongly) agreed that undergoing surgery was the right decision and 79% of the patients in the anti-TNF arm (strongly) agreed, 14% neither agreed nor disagreed and 7% disagreed that anti-TNF treatment was the right decision. Conclusion: This study further supports the previous finding that anti-TNF induction combined with surgical closure should be considered in patients with Crohn's perianal fistulas as long-term outcomes are favourable. Interestingly, surgical closure does not seem to be correlated to decreased continence, and all patients agreed that surgery was the right decision.